2016
DOI: 10.1161/jaha.116.003774
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Vanilloid 1 Regulates Mitochondrial Membrane Potential and Myocardial Reperfusion Injury

Abstract: BackgroundThe transient receptor potential vanilloid 1 (TRPV1) mediates cellular responses to pain, heat, or noxious stimuli by calcium influx; however, the cellular localization and function of TRPV1 in the cardiomyocyte is largely unknown. We studied whether myocardial injury is regulated by TRPV1 and whether we could mitigate reperfusion injury by limiting the calcineurin interaction with TRPV1.Methods and ResultsIn primary cardiomyocytes, confocal and electron microscopy demonstrates that TRPV1 is localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 53 publications
1
51
0
Order By: Relevance
“…If cardiac protection was neuron mediated, the ability for ischaemic preconditioning to reduce myocardial infarct size should not be abolished in an isolated heart model. We and others recently identified that TRPV1 is present and functional within the cardiac myocyte (Andrei et al, ; Hurt et al, ). TRPV1 also modulates myocardial ischaemia‐reperfusion injury through the regulation of mitochondrial membrane potential (Hurt et al, ).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…If cardiac protection was neuron mediated, the ability for ischaemic preconditioning to reduce myocardial infarct size should not be abolished in an isolated heart model. We and others recently identified that TRPV1 is present and functional within the cardiac myocyte (Andrei et al, ; Hurt et al, ). TRPV1 also modulates myocardial ischaemia‐reperfusion injury through the regulation of mitochondrial membrane potential (Hurt et al, ).…”
Section: Discussionmentioning
confidence: 83%
“…Capsaicin (CAP) cream (0.1%; CVS Pharmacy, Woonsocket, Rhode Island, USA) was administered on the abdomen. The doses of morphine and capsazepine were determined from previous studies using our rodent myocardial ischaemia‐reperfusion model (Gross et al, ; Small et al, ; Hurt et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ASICs and TRPV1 are mainly found in the nervous system, both channels have also been reported to express in cardiovascular systems1617182324, however, there is no evidence for their distribution in the heart. Here, we first demonstrated the presence of the mRNAs and proteins of ASIC1, 2 and 3 in the cultured myocardiac cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is a tetrameric membrane protein composing of four identical subunits, and each subunit contains six transmembrane regions to form a non-selective cation channel with high permeability to Ca 2+  14. Although TRPV1 is firstly identified in sensory neurons in 199715, it is also identified in other tissues, especially in the cardiovascular system, including vascular smooth muscle cells, vascular endothelial cells16, and the mitochondria of cardiomyocytes17. Activation of TRPV1 channel by capsaicin has been reported to improve endothelium - dependent vasorelaxation and prevent hypertension18, Myocardial reperfusion injury is also reported to be mitigated by limiting the interaction between TRPV1 and calcineurin17.…”
mentioning
confidence: 99%